Retinal Vein Changes as a Biomarker to Guide Diagnosis and Management of Elevated Intracranial Pressure - Moss, Heather E. (Frontiers in Neurology, 2021)
Retinal vein changes, which can be observed on clinical exam or ophthalmic imaging, are promising non-invasive biomarkers for elevated intracranial pressure (ICP) as a complement to other markers of high ICP including optic nerve head swelling. Animal and human studies have demonstrated increase in retinal vein pressure associated with elevated ICP mediated by increase in cerebral venous pressure, compression of venous outflow by elevated cerebral spinal fluid pressure in the optic nerve sheath, and compression of venous outflow by optic nerve head swelling. Retinal vein pressure can be estimated using ophthalmodynamometry. Correlates of retinal vein pressure include spontaneous retinal venous pulsations, retinal vein diameter, and retinal vein tortuosity. All of these have potential for clinical use to diagnose and monitor elevated ICP. Challenges include diagnostic prediction based on single clinical measurements and accurate assessment of retinal vein parameters in cases where optic nerve head swelling limits visualization of the retinal veins.